The characterisation and determinants of quality of life in ANCA associated vasculitis - Basu, N; McClean, A; Harper, L; Amft, E; Dhaun, N; Luqmani, R; Little, M; Jayne, D; Flossmann, O; McLaren, J; Kumar, V; Erwig, L; et al. (2014)
Objectives To contextualise and identify the determinants of poor health related quality of life (QOL) among patients with antineutrophil cytoplasm antibody (ANCA) associated vasculitis (AAV). Methods A multicentre AAV case-control study was conducted using two matched groups of population and chronic disease controls. Measures of physical and mental QOL as well as putative bio-psychosocial determinants of QOL impairment were collected. Concurrently, putative clinical QOL determinants were recorded. Conditional logistic regression analyses characterised group differences while multivariable logistic regression identified within-case QOL associations which were further quantified using population attributable risks (PAR). Results Cases (n=410) experienced similar QOL to chronic disease controls (n=318) ( physical QOL: OR 0.7, 95% CI 0.4 to 1.1; mental QOL: OR 1.1, 95% CI 0.8 to 1.6). However, they were substantially more likely to report poor QOL compared to general population controls (n=470) ( physical QOL: OR 7.0, 95% CI 4.4 to 11.1; mental QOL: OR 2.5, 95% CI 1.7 to 3.6). A few clinical, but many more bio-psychosocial factors were independently associated with poor QOL. In population terms, fatigue was found to be of principal importance (physical QOL: PAR 24.6%; mental QOL: PAR 47.4%). Conclusions AAV patients experienced significant QOL impairment compared to the general population, but similar to those with other chronic diseases whose considerable needs are already recognised. Potentially modifiable clinical determinants have been identified; however bio-psychosocial interventions are likely to provide the greater QOL gains in this patient population.